Analysis between preoperative cervical radiographic parameters represented by the K-line tilt and the short-term prognosis of laminoplasty for posterior longitudinal ligament ossification: A retrospective study - Wei, Baixing; Liu, Wanting; Wu, Han (Frontiers in Surgery, 2022)
OBJECTIVES: To investigate the relationship between preoperative radiographic parameters and the short-term prognosis of patients with cervical ossification of the posterior longitudinal ligament (OPLL) who underwent laminoplasty (LAMP). METHODS: A retrospective analysis of Cervical OPLL 50 patients with K-line (+) OPLL with no cervical kyphosis who received LAMP was performed. Based on preoperative neutral position X-ray, the K-line tilt, C2-C7 SVA (sagittal vertical axis), CL (cervical lordosis), T1 slope, and T1 slope-CL were recorded. The JOA (Japanese Orthopaedic Association Scores) score and the cervical kyphosis change were recorded one year after surgery. Patients were divided into good and poor prognosis groups according to the median (12.5) of the postoperative JOA score. RESULTS: There were differences between the two groups in K-line tilt, C2-C7 SVA, and T1 slope (all Ps < .05). There was a strong linear correlation between the three, K-Line tilt, JOA score, and C2-C7 SVA. The degree of influence of K-line tilt, C2-C7 SVA, T1 slope on postoperative JOA score was analyzed using multiple linear regression, and the absolute value of the standardized coefficient Beta were 0.550, 0.319, 0.185, respectively. There was no cervical kyphosis change one year after surgery. CONCLUSION: As preoperative cervical parameters, the influence of K-line tilt, C2-C7 SVA, and T1 slope on postoperative JOA score decreases in order. There was a linear relationship between preoperative K-line tilt and postoperative JOA score, implying that patients with cervical OPLL with high K-line tilt were not eligible for LAMP. K-line tilt was not predictive of cervical kyphosis change after LAMP in patients with OPLL at short-term follow-up.